Evoking 21st-Century Skills: Developing Instrument of Critical Thinking Skills and Mastery of Ecosystem Concepts - Harahap, Lia Junita; Ristanto, Rizhal Hendi; Komala, Ratna (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
Instrument is one of the supports of learning success. Assessment of student knowledge will encourage students to get better grades and will have an impact on increasing student knowledge. This study aims to develop the instruments of critical thinking skills and the ecosystem concept mastery. The instruments produced were an essay test adopted from Facione and a multiple-choice test adopted from Anderson & Krathwohl. This research was conducted on September 2018 - October 2019 with 37 tenth-grade students as the sample. The research method used was the 4D model (Define, Design, Develop, and Disseminate), however this research did not do the disseminate stage due to the limitation of time. The results showed that the instruments are feasible with the results of expert validation of 81.03 and 85.00 respectively. Based on the results of the study, it can be concluded that the developed instruments could be used to measure the critical thinking skills and mastery of concepts. However, these tests must be developed further in large classes with more students.